1996
DOI: 10.1063/1.115759
|View full text |Cite
|
Sign up to set email alerts
|

A ferroelectric transparent thin-film transistor

Abstract: Müller, G.; Cillessen, J.F.M.; Giesbers, J.B.; Weening, R.P.; Wolf, R.M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
115
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(116 citation statements)
references
References 12 publications
0
115
0
1
Order By: Relevance
“…Oxide TFTs have a long history that extends from the mid-1960s [34,35], but there was a long lull until the report of SnO 2 :Sb TFTs combined with a ferroelectric gate in 1996 [36], although some unpublished development work had been conducted. Th e oxide TFT fever started in 2003 with reports of several crystalline oxide TFTs using ZnO [37][38][39][40] and InGaZnO 4 [41] channels.…”
Section: Brief History Of Aossmentioning
confidence: 99%
“…Oxide TFTs have a long history that extends from the mid-1960s [34,35], but there was a long lull until the report of SnO 2 :Sb TFTs combined with a ferroelectric gate in 1996 [36], although some unpublished development work had been conducted. Th e oxide TFT fever started in 2003 with reports of several crystalline oxide TFTs using ZnO [37][38][39][40] and InGaZnO 4 [41] channels.…”
Section: Brief History Of Aossmentioning
confidence: 99%
“…After a few decades of silence, in 1996 metal oxide semiconductors gained new attention as active layers in ferroelectric memory TFTs. 49,50 The pioneering work of Prins et al demonstrated the first fully transparent and metal oxide-based TFT with antimony-doped SnO 2 (SnO 2 :Sb) semiconductor grown by pulsed layer deposition (PLD) (Fig. 2).…”
Section: A Historical Perspectivementioning
confidence: 99%
“…Metal oxide semiconductors, in particular, are very attractive for implementation into thin-film transistors (TFTs) [1][2] mainly because of their high charge 2 carrier mobility, high optical transparency, excellent chemical stability, mechanical stress tolerance and processing versatility [3][4][5] . Oxide semiconductors are usually grown using vacuum-based techniques such as sputtering [6][7][8] , pulsed laser deposition [9] , chemical vapour deposition [10] , and ion-assisted deposition [11][12] .…”
mentioning
confidence: 99%